Desenvolvimento de eletrodo modificado com o solvente eutético profundo cloreto de colina/glicerol para a determinação simultânea de paracetamol e diclofenaco - Piton, Gabriela Rizzo (Universidade Federal de São Carlos, 2021)
In this master’s dissertation has investigated the use of deep eutectic solvents (DES) for the development of electrochemical sensors. DES was immobilized on the surface of a glassy carbon electrode (GCE) within carbon black (CB) nanoparticles in chitosan (CTS) films crosslinked with epichlorohydrin (ECH). During the electroanalytical method development for the simultaneous determination of acetaminophen (ACP) and diclofenac (DCF), the experimental conditions were optimized, such as composition and concentration of the DES within the modification, support electrolyte’s pH, time, and applied potential for the analytes pre-concentration, and instrumental parameters for the differential pulse adsorptive anodic stripping voltammetry technique (DPAdASV). The DES applied in this work were characterized by Fourier-transform infrared spectroscopy and conductivity measurements. The proposed modified electrode had its morphological structure characterized by scanning electronic microscopy, which allowed to observe morphological changes after incorporating DES into the CB film. The electrochemical characterization was given by electrochemical impedance spectroscopy to calculate electronic parameters, such as capacitance and charge transfer resistance, and by cyclic voltammetry to calculate the heterogeneous electron transfer constant (k0). The DPAdASV method resulted in linear responses in the range from 5.0 × 10−7 to 3.9 × 10−6 mol L−1 for ACP and from 5.0 × 10−7 to 1.5 × 10−5 mol L−1 for DCF, with limits of detection of 2.7 × 10−8 mol L−1 and 5.2 × 10−8 mol L−1 for ACP and DCF, respectively. The proposed method proved to be precise and selective, observed from studies of repeatability and effect of possible interferents besides addition and recovery studies. The accuracy of the proposed method was evaluated for the simultaneous determination of ACP e DCF in commercial pharmaceutical samples and biological fluids (synthetic urine and bovine serum). The obtained results were compared with those obtained by HPLC/UV-Vis.
Development of a choline chloride/glycerol deep eutectic solvent modified electrode for the simultaneous determination of acetaminophen and diclofenac
Keywords: Solventes eutéticos profundos; Sensores; Eletroanalítica; Deep eutectic solvents; Sensors; Electroanalysis; Carbon black; CIENCIAS EXATAS E DA TERRA::QUIMICA